Large fractal dimension of chaotic at tractor for earthquake sequence near Nurek reservoir - BHATTACHARYA, S. N.; RAY, K.C. SINHA; SRIVASTAVA, H. N. (MAUSAM, 1995)
Fractal dimension of the chaotic attractor for earthquake sequence in Nurek dam based on 22.000 earthquakes detected during the period 1976-87 has been studied for this total period of observations as well as for the period from December 1977 to December 1987. The second period excluded increased seismic activity during second stage of filling the reservoir. Large fractal dimensions of the chaotic at tractor of 8.3 and 7.3 were found for the respective period which suggests the complexity of earthquake .dynamics in this region as compared to Koyna reservoir.